KERAGAAN USAHATANI PETANI MISKIN PADA LAHAN KERING DAN SAWAH TADAH HUJAN (STUDI KASUS DI KABUPATEN TEMANGGUNG) - AMAR K. ZAKARIA; DEWA K.S. SWASTIKA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
The Performance of Poor Farmers' Farming in Dryland and Rainfed Lowland: (The CaseStudy in Temanggung, Central Java). The Poor Farmers Income Improvement ThroughInnovation Project (PFI3P) is aimed to introduce some innovation for poor farmers, toenable them to solve their own problems. The project will provide them with appropriateagricultural technology as well as development of infrastructure facilities. Temanggung isone among five districts in Indonesia that granted ADB-funded Project for empowermentof poor farmers. Before project been implanted, the baseline survey was conducted. Theobjective of the survey is to get better understanding regarding social economic conditionof involved farmers, in advance to PFI3P implementation. The survey took place in fivevillages, and 30 farmers in each village were chosen as samples. The results of the studyshowed that the return cost ratio (R/C) for rice farming was 1.28, meaning that every singlerupiah spent for rice farming the gross return was 1.28. Meanwhile, the R/C ratio for cornwas 1.27. These relatively low R/C were mainly due to low yield of both rice and corn. Onthe other hands, the R/C for chili and tobacco were 2.82 and 2.60, respectively, indicatinghigh profit earned from these two case crops. Therefore, the contributions of these crops tothe household income were relatively high compared to food crops.